Investment Duration and Corporate Governance1. (February 2015) - Lee, Youngjoo; Chung, Kee H.
Abstract: In this study we analyze the relation between institutional investment duration and corporate governance using a new metric of investment duration that accounts for firm‐specific investment durations of each institution. We conjecture that institutional investors that hold a firm's shares for a longer duration have greater incentives and ability to influence the firm's governance structure. Consistent with this conjecture, we find that a broadly defined index of corporate governance increases with the duration of institutional ownership. We also show that the relation between investment duration and corporate governance varies across different types of institutions and across firms with different stock market liquidities.